2006
DOI: 10.1002/cncr.21784
|View full text |Cite
|
Sign up to set email alerts
|

Down‐regulation of locus‐specific human lymphocyte antigen class I expression in Epstein–Barr virus‐associated gastric cancer

Abstract: Clinical course and prognosis are variable among patients with chronic inflammatory demyelinating polyneuropathy (CIDP), whereas the extent of axonal degeneration is the major prognostic factor. We studied the effects of sera from CIDP patients on axonal growth in cultured mouse dorsal root ganglion neurons. Compared with control sera, CIDP sera prominently suppressed axonal outgrowth of dorsal root ganglion neurons and shortened axonal length. The inhibitory activity was abolished by adding Y27632, a Rho‐kina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 63 publications
2
19
0
Order By: Relevance
“…Importantly, HLA-E protein expression was strongly associated with expression of classical HLA molecules (class I and class II) and components of the antigen processing machinery (immunoproteasome, peptide transporter TAP, trimming enzyme ERAP, and chaperone Erp57) ( Table 1). This association implies that tumor expression of HLA-E is regulated in a comparable fashion to classical HLA and that its presence on tumors is not a defense mechanism against NK cell-mediated lysis in classical class I-negative tumors, as sometimes suggested in the literature (26,(29)(30)(31). Instead, our data argue that HLA-E expression arises in the setting of an intact antigen processing apparatus and, in ovarian cancer, abundant CTL infiltration.…”
Section: Discussionsupporting
confidence: 65%
“…Importantly, HLA-E protein expression was strongly associated with expression of classical HLA molecules (class I and class II) and components of the antigen processing machinery (immunoproteasome, peptide transporter TAP, trimming enzyme ERAP, and chaperone Erp57) ( Table 1). This association implies that tumor expression of HLA-E is regulated in a comparable fashion to classical HLA and that its presence on tumors is not a defense mechanism against NK cell-mediated lysis in classical class I-negative tumors, as sometimes suggested in the literature (26,(29)(30)(31). Instead, our data argue that HLA-E expression arises in the setting of an intact antigen processing apparatus and, in ovarian cancer, abundant CTL infiltration.…”
Section: Discussionsupporting
confidence: 65%
“…Correspondingly, defective expression of various APM components was recently shown to be associated with progression and survival in various human tumors, particularly those associated with oncogenic viral infections (Facoetti et al, 2005;Meissner et al, 2005;Dutta et al, 2006;Seliger et al, 2006). Cervical carcinoma is an important example where the down-regulation of APM components, particularly TAP, has been demonstrated to be an important phenomenon in tumor progression (Cromme et al, 1994a,b;Keating et al, 1995;Ritz et al, 2001).…”
Section: Introductionmentioning
confidence: 96%
“…Furthermore, a number of earlier reports (Diepstra et al, 2005;Huang et al, 2012;Su et al, 2013) have shown several EBV associated carcinomas including Hodgkin's Lymphoma and Nasopharyngeal Carcinoma to display downregulation of the HLA Class 1 loci (Diepstra et al, 2005;Huang et al, 2012;Sengupta et al, 2006; Su et al, 2013). Moreover, earlier studies from our group have also shown EBV associated gastric cancer to be associated with HLA Class I downregulation (Dutta et al, 2006). We therefore further proceeded to pin point the EBV latency I gene that may be bringing about the decrease HLA Class Ia expression in gastric cancer cells.…”
Section: Introductionmentioning
confidence: 90%
“…Having known that EBV positive Korean gastric cancer cells do decrease HLA ABC expression (Dutta et al, 2006), we first proceeded to determine the EBV latent gene which may be bringing about this effect. We targeted the two main genes detected in most gastric cancer samples viz; LMP2A and EBERs.…”
Section: Ebv Lmp2a Decreases Hla Abc Expressionmentioning
confidence: 99%
See 1 more Smart Citation